2011
DOI: 10.3892/ol.2011.267
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression status of p53 and epidermal growth factor receptor in thymoma

Abstract: Abstract. Evaluating the state of malignancy of thymoma is a challenge due to the discrepancies between pathological classifications and clinical stage criteria. Therefore, the identification of markers contributing to the assessment of the stage of malignancy of thymoma would be useful. This study aimed to evaluate the prevalence of p53 and epidermal growth factor receptor (EGFR) in thymoma, demonstrate the clinical significance and assess the potential of specifictargeted therapy. A total of 16 thymic hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Data associated with various IHC expressions of TC and TM were extracted from each of the eligible studies [ 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Two independent authors extracted all of the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data associated with various IHC expressions of TC and TM were extracted from each of the eligible studies [ 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Two independent authors extracted all of the data.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Nakagawa et al reported that the combination of CD117 and CD5 was useful for differentiating between thymic and lung squamous cell carcinoma [ 8 ]. Insulin-like growth factor-1 receptor (IGF-1R) was proposed as a potential therapeutic target for TET and is more frequently expressed in TC than in TM [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bone morphogenetic protein-7 expression reflects the high proliferative ability and aggressiveness of thymic epithelial tumors their biological behaviors, the classification of thymic epithelial tumors remains challenging. Although several factors, such as podoplanin, p53, Ki-67, and GLUT-1, have been reported to be associated with the individual biological behavior of thymic epithelial tumors (3)(4)(5)(6)(7), more unique markers which reflect the biology of thymic epithelial tumors are required. In order to detect the expression of molecules that are important for the progression of thymic epithelial tumors, we compared gene expression profiles using microarray analysis between the normal thymus and type B2 thymoma in clinical specimens obtained in our department.…”
Section: Original Articlementioning
confidence: 99%